PENERAPAN NILAI ISLAMI DALAM PELAYANAN FARMASI KLINIS: KAJIAN SISTEMATIS ETIKA, KEHALALAN DAN KEPUASAN PASIEN - Rozak, Miftahul; Saraswati, Damai Ira; Fathurohman SW, Oman; Salamah, Nina (JURNAL KAJIAN ISLAM MODERN, 2025)
Islamic pharmaceutical and healthcare services represent an innovative approach that integrates Islamic ethical values, such as justice, halal compliance, and patient satisfaction, into clinical practice. However, the application of these values faces challenges, including public knowledge gaps, insufficient training for healthcare professionals, and the lack of unified practice standards. This study employs a systematic review method to analyze relevant literature from the past decade. Literature searches were conducted using PubMed and Google Scholar with keywords such as "Islamic values in clinical pharmacy," "halal pharmaceuticals," and "maqasid shariah in healthcare." Articles meeting inclusion criteria were evaluated following PRISMA guidelines and analyzed qualitatively to identify key findings and research gaps. After the selection process, six articles met the inclusion criteria.. The findings reveal that integrating Islamic values, such as halal pharmaceuticals, Islamic ethics, and sharia-based facilities, significantly contributes to improving pharmaceutical service quality, patient satisfaction, and loyalty among Muslim patients. However, implementation remains constrained by a lack of healthcare professional training, minimal regulations, and incomplete societal perceptions. This review highlights the importance of developing an integrated framework, enhancing public and professional education, and fostering cross-professional collaboration to support the integration of Islamic values in healthcare services. This approach holds great potential to enhance service quality, patient satisfaction, and loyalty while serving as an innovative model for universal healthcare services.